2020
DOI: 10.3390/fi12090150
|View full text |Cite
|
Sign up to set email alerts
|

Integrating IP Mobility Management Protocols and MANET: A Survey

Abstract: The Mobile ad hoc Network (MANET) is a collection of mobile devices that forms a self-created, self-administered, and self-organized network. It is an infrastructureless network that does not require an existing infrastructure to operate. MANET suits scenarios where a temporary network is needed, such as emergency rescue, the military field, and disaster areas. MANET is an isolated network, and communication is restricted to the participating nodes’ transmission coverage. In order to increase its connectivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Also, the proposed algorithms enable versatile uplink, and downlink slot allocation to be modified, endorses half-duplex and full-duplex modes by significant performance improvements. Specifically, the proposed protocols can achieve different efficiency criteria with point-to-multipoint communications and point-to-point communications through specific importance on data transmission in the vehicle group examined by 5G standardization organizations and testing activities [39].…”
Section: Summarization Of Our Proposed Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the proposed algorithms enable versatile uplink, and downlink slot allocation to be modified, endorses half-duplex and full-duplex modes by significant performance improvements. Specifically, the proposed protocols can achieve different efficiency criteria with point-to-multipoint communications and point-to-point communications through specific importance on data transmission in the vehicle group examined by 5G standardization organizations and testing activities [39].…”
Section: Summarization Of Our Proposed Workmentioning
confidence: 99%
“…The different experiments' simulation findings demonstrate that OFACA-5G fits well into specific MANET environments and permits effective routing high PDR and small or equivalent end-to-end latency and overhead. This study examined the effectiveness of some well-known routing protocols for mmWave frequency bands for MANETs [39]. This study demonstrated how mmWave frequencies would improve the network capacity and transmission ratio.…”
Section: Performance Under Sybil Attacksmentioning
confidence: 99%
“…A survey on the performance of different routing protocols under Transmission Control Protocol (TCP) congestion control algorithms in MANET. 2020 [2] A survey on different types of attacks and security issues to MANET layers, MANET topology 2019 [3] A survey summarizes existing excellent research to defog uncertainties regarding the practical implementation of MANETs 2021 [4] A survey of the use of mobility management systems analyzes the existing integrating of MANET with the internet. 2020 [5] A Survey on Power-Aware Optimization Solutions and design challenges for MANETs 2020 [6] A survey of the main types of attack at the network layer, protection mechanisms, detection algorithms in MANET 2013 [7] A survey of various techniques to solve the problem of energy efficiency and load balancing in MANET.…”
Section: Manet [1]mentioning
confidence: 99%